Forces applied with a hoof tester to cadaver feet vary widely between users. (16th February 2013) - Arndt, J. L.; Pfau, T.; Day, P.; Pardoe, C.; Bolt, D. M.; Weller, R.
Abstract : Hoof testers are commonly used in equine practice. In this study, we determined the intraoperator and interoperator reliability of force application with hoof testers for different groups: experienced veterinarians, novices and farriers. For this purpose, we have developed and validated an instrumented hoof tester. Forces varied significantly between the different regions of the foot for experienced operators applying the highest forces to the heels, then the frog, then the toe, and the lowest forces to the quarters. Novices applied significantly more force to the toe versus the frog. Intraoperator reliability varied significantly between regions and operators. Novices had the narrowest width of limits of agreement for the frog and heel, but the widest for the toe and the quarters, whereas farriers had the narrowest width of agreement for the toe and quarter. Force application differed significantly between groups for the frog and heel regions, but not the toe and quarters. Veterinarians applied higher forces to the frog compared with farriers and novices, and higher forces to the heel compared with novices. This study showed that hoof tester forces vary widely within and between operators, and standardisation of hoof tester use is needed to make this diagnostic test more reliable.